Metode Pengukuran Peralatan Localizer di Bandar Udara (Studi Kasus Bandar Udara Sam Ratulangi-Manado) - Feti Fatonah (Research and Development Agency of The Ministry of Transportation, 2014)
In accordance with the Rules of DGCA number: 83 2005, about the testing procedures on the ground (ground inspection) equipment electronics and electrical facilities, the cost of all existing facilities at the airport including ILS localizer testing should be carried out on land with parameters determined in order to maintain the operational performance of equipment in accordance with the standards and operational requirements that have been set. And in accordance with ICAO Annex 10 Document 8071, then to determine the performance of the localizer equipment mandatory calibration flight. This calibration flight periodically for localizer equipment provisions must be implemented four months in which the airport in cooperation with the Ministry of Transportation calibration.Sesuai dengan Peraturan dari Direktorat Jenderal Perhubungan Udara nomor : 83 tahun 2005, tentang prosedur pengujian di darat ( ground inspection ) peralatan fasilitas elektronika dan listrik penerbangan maka semua fasilitas yang ada di Bandara termasuk ILS, Localizer harus dilaksanakan pengujian di darat dengan parameter yang telah ditentukan guna mempertahankan kinerja operasional peralatan sesuai dengan standard dan persyaratan operasional yang telah ditetapkan. Dan sesuai dengan annex 10 Document 8071 ICAO, maka untuk mengetahui kinerja dari peralatan localizer maka wajib dilakukan penerbangan kalibrasi. Penerbangan kalibrasi ini berkala untuk peralatan localizer ketentuannya harus dilaksanakan 4 bulan sekali dimana pihak Bandar udara bekerja sama dengan Balai kalibrasi Kementerian Perhubungan.